2021
DOI: 10.3390/d13080367
|View full text |Cite
|
Sign up to set email alerts
|

Seeding Resilient Restoration: An Indicator System for the Analysis of Tree Seed Systems

Abstract: Achieving multi-million-hectare commitments from countries around the world to restore degraded lands in resilient and sustainable ways requires, among other things, huge volumes of tree planting material. Seed systems encompassing all forest reproductive material (e.g., seeds, cuttings, stakes, and wildings), are key to ensuring that sufficient planting material with a diverse range of suitable species, adapted to local conditions and capable of persisting under a changing climate, is available for restoratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…The use of high-quality planting material guarantees the success of seed-based restoration programs [77], and selection of forest restoration material with priority areas for sourcing seeds can be supported by provenance comparisons reported in our studies (Figure 2) because oxidation processes reported in stored seeds are transferred to seedlings [27]. Provenance selection determines the growth performance of Q. robur [78]; in this context, seeds of Parczew provenance quickly losing vitality should not be considered for long-term storage and reforestation purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The use of high-quality planting material guarantees the success of seed-based restoration programs [77], and selection of forest restoration material with priority areas for sourcing seeds can be supported by provenance comparisons reported in our studies (Figure 2) because oxidation processes reported in stored seeds are transferred to seedlings [27]. Provenance selection determines the growth performance of Q. robur [78]; in this context, seeds of Parczew provenance quickly losing vitality should not be considered for long-term storage and reforestation purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Our assessment reveals that the frameworks underlying the national tree seed systems vary between countries, likely as a result of geographical, historical and cultural differences [22,54]. Some of the strengths and weaknesses identified in this study can be directly associated with these underlying frameworks.…”
Section: Discussionmentioning
confidence: 81%
“…Further research is needed to understand how informal tree seed systems operate under different policy and socio-economic contexts and how operators can be supported to participate in formal seed markets. We therefore recommend adding a new indicator to the indicator set proposed by Atkinson et al [54], addressing the involvement of local communities in seed production and the existence of related incentives and extension to support their role.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations